Coming In? Or Going Out? A Few Thoughts on Theological Education. (December 2014) - Haemig, Mary Jane
Abstract Much of theological education and church life has been based on the assumption that people will come to church. Instead, the church needs to look at how it can go out to those who do not come. Careful consideration needs to be given to the traits of leaders needed for this task and the ethos of the education best suited to helping them move out. The past provides some models that may be useful for Lutherans today.